Impact of Fecal Microbiota Transplantation on Digestive Tract Colonization due to Carbapenem-resistant Enterobacteriacae and Vancomycin-resistant Enterococci. (4th October 2017) - Davido, Benjamin; Batista, Rui; Michelon, Hugues; Escaut, Lelia; Fessi, Hafedh; Senard, Olivia; Matt, Morgan; Deconinck, Laurene; De Truchis, Pierre; Salomon, Jérôme; Dinh, Aurelien
Abstract: Background: Fecal Microbiota Transplantation (FMT) has proved to be an efficient therapy for recurrent C. difficile infection. Its indication is currently discussed for the decolonization of Multidrug-resistant organisms (MDRO) on the basis of mice experiments. Two recent publications suggest that it could be an efficient strategy for patients colonized with digestive MDRO colonization but few data are available for Carbapenem-Resistant Enterobacteria (CRE) and Vancomycin-Resistant Enterococcus (VRE) colonization. Methods: We performed a FMT among patients colonized by CRE or VRE documented by at least 3 nonconsecutive positive swabs (including one in the week prior to the FMT). Procedure: 2 days prior to the FMT, patients received a proton pump inhibitor and a naso-duodenal tube was inserted to perform a bowel lavage with X-prep. FMT was performed with frozen feces from 4 donors previously screened for potential diseases using 5 syringes of 50 cc of feces diluted with saline. Patients were discharged after 24h and benefited of outpatient control swabs (PCR + culture) on day 7, 14, 21, 28 and each month during 3 months in order to assess the decolonization. The study is registered at ClinicalTrials.gov (NCT03029078). Results: Seventeen individuals were included. Mean age was 69 ± 12.7 (SD) years. Eight patients were positive for CRE (KPC, OXA48 or NDM-1) and 9 for VRE. All suffered from severe underlying condition (hemodialysis, dementia, cirrhosis) or chronic wounds. Median functional autonomy scale was evaluated using the French Iso-Resources Groups (GIR)=4/6 IQR[3–6] supporting they were dependent persons. At 1-month follow-up, 3/8 patients were free from CRE and 5/9 from VRE. At 3-month follow-up, 3/8 patients were still free from CRE whereas 7/8 were free from VRE, considering one death from cirrhosis. Moreover, one of them received antibiotics during a week for a hospital-acquired infection a long time after FMT. No adverse events were reported. Conclusion: FMT seems to be an attractive option to eradicate colonization of MDRO, especially for VRE. Limited data are available in the literature to determine response factors. Meanwhile its efficacy is moderate; it provides an alternative solution to quarantine for fragile and frequently hospitalized patients. More data and a controlled trial are required. Disclosures: All authors: No reported disclosures.